2019
DOI: 10.1037/hea0000797
|View full text |Cite
|
Sign up to set email alerts
|

Momentary precipitants connecting stress and smoking lapse during a quit attempt.

Abstract: Objective: Most attempts at smoking cessation are unsuccessful, and stress is frequently characterized both as a momentary precipitant of smoking lapse and a predictor of subsequent changes in other key precipitants of lapse. The current study examined longitudinal associations among stress, multiple precipitants of lapse, and lapse among smokers attempting to quit. Method: Ecological momentary assessments (EMAs) were gathered from a multiethnic, gender-balanced sample of 370 adults enrolled in a smoking cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
3
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 55 publications
6
23
3
1
Order By: Relevance
“…These findings challenge the relapse prevention models, which emphasise the role of positive outcome expectancies as precipitants to relapse and posit that there are feedback loops between transient changes in positive outcome expectancies and gambling episodes [ 12 , 13 ]. They are also inconsistent with previous EMA substance use research demonstrating that these expectancies are phasic determinants of smoking and alcohol consumption [ 50 , 51 , 52 ] and previous cross-sectional research demonstrating a significant relationship between positive gambling outcome expectancies and problem gambling [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…These findings challenge the relapse prevention models, which emphasise the role of positive outcome expectancies as precipitants to relapse and posit that there are feedback loops between transient changes in positive outcome expectancies and gambling episodes [ 12 , 13 ]. They are also inconsistent with previous EMA substance use research demonstrating that these expectancies are phasic determinants of smoking and alcohol consumption [ 50 , 51 , 52 ] and previous cross-sectional research demonstrating a significant relationship between positive gambling outcome expectancies and problem gambling [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Although EMA methodologies are increasingly being employed in the gambling field [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], none have yet examined the relationships between situational (phasic) outcome expectancies and gambling behaviour. This is in contrast to other addictions literature, in which there is EMA evidence suggesting that positive outcome expectancies predict the occurrence and amount of smoking and alcohol consumption [ 50 , 51 , 52 , 53 ], moderate the relationships between other situational factors and the likelihood of drinking [ 53 ], play a mediating role between other situational factors and smoking/alcohol consumption [ 54 , 55 , 56 , 57 ], are associated with smoking self-efficacy and craving [ 58 ], and reduce non-smoking intentions [ 58 ].…”
Section: Introductioncontrasting
confidence: 90%
“…Evidence also indicates that perceived stress is a barrier for smoking cessation. Persons with high level of stress (PTSD) have lower odds of quitting 25 and in prospective studies of smokers enrolled in a smoking cessation program, stress predicted relapse 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial stress, also referred to as psychological stress, is the degree to which a person perceives that a situation exceeds their ability to cope (Cohen & Janicki-Deverts, 2012). Psychosocial stress (hereinafter simply referred to as stress) is a construct that can fluctuate quickly in response to a specific event (e.g., taking an exam) or change gradually in response to cumulative stimuli that can diminish the ability to cope (Barbosa-Leiker et al, 2013;Cambron, et al, 2019). Stress is highly correlated with symptoms of depression and anxiety; therefore, it has been suggested that these three constructs may form part of a broader construct (psychological distress; Henry & Crawford, 2005).…”
Section: Introductionmentioning
confidence: 99%